Demand of organic products from grocery shops in Luang Prabang, Lao PDR - LOUNBANDITH, Nouphit; SOMSAMONE , Vilayphone; BOUNTHIDETH, Thepduangchan (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Tourism is considered as a main economic activities for driving Luang Prabang economy. The increases of tourist arrivals also demand of agricultural production. Local farmers uses chemical fertilizer and pesticide for more productivity. In fact, the tourist prefers having organic food for two reasons, the first reason is forhealth and the second is environmental friendly purposes. The government of Lao PDR adapted the international agenda on international Federation of Agricultural Movement-IFOAM to create organic standard regulation for Lao PDR. In order to promote organic production to meet the demand of tourist consumption behavior on food and beverage when traveling to Luang Prabang. This study focuses on two objectives, including (1) the phenomenal of organic production and farming in Luang Prabang and (2) demand of organic products from grocery shops in urban Luang Prabang. The secondary data is used for data analysis of objective one and 180 questionnaires are designed as sampling. Four markets in urban Luang Prabang are used as a case study such as Naviengkham, Pakham, Phongsavan, and Phosi market. The findings show that organic farming and production activities in LuangPrabang firstly supported by international agency and local government to operate organic farmers group. Currently there are two centers are known for organic product market fair. The first center is operated every early Wednesday and Saturday at Department of Agriculture and Forestry, and the second center is operated every Monday and Thursday around 16:00. It still needs more legislation practices on organic trade mark and improve variety of products. The demand of the grocery shops from the market shows that pork is the highest demand within amount of 180 kg in daily, beef, chicken, duck, fish and frog. For the vegetables the highest demand is the Chinese vegetable with amount of 618 Kgs per day, followed by morning glory, lettuce, tomatoes, and ingredients.